Proceedings of the 11th International Conference on Interaction Design and Children 2012
DOI: 10.1145/2307096.2307131
|View full text |Cite
|
Sign up to set email alerts
|

Group interaction on interactive multi-touch tables by children in India

Abstract: Interactive tables provide multi-touch capabilities that can enable children to collaborate face-to-face simultaneously. In this paper we extend existing understanding of children's use of interactive tabletops by examining their use by school children in a school in Delhi, India. In the study, we explore how the school children exhibit particular types of collaboration strategies and touch input techniques when dealing with digital objects. In particular, we highlight a number of behaviours of interest, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
0
7
0
6
Order By: Relevance
“…It is likely that egocentrism may have important implications for large-screen tabletop designs and situations in which children need to work collaboratively, such as in Jamil et al, 2012;Mansor et al, 2008). For such scenarios, children may encounter difficulties during collaboration simply because of their inabilities to understand correctly their peers' viewing angles of the shared workspace.…”
Section: Implications For Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that egocentrism may have important implications for large-screen tabletop designs and situations in which children need to work collaboratively, such as in Jamil et al, 2012;Mansor et al, 2008). For such scenarios, children may encounter difficulties during collaboration simply because of their inabilities to understand correctly their peers' viewing angles of the shared workspace.…”
Section: Implications For Designmentioning
confidence: 99%
“…The authors found that children develop strategies to obtain the control over the tabletop from another child (i.e., turn-taking), that they use the entire available surface of the tabletop, and also showed how children's positions around the tabletop affect where they touch the screen Jamil et al (2012). observed other collaboration forms, such as children (aged 11 to 13 years) moving together objects on the surface of the interactive tabletop.…”
mentioning
confidence: 99%
“…Previous work has shown that simultaneous interaction with digital objects on tabletops is an integral part of collaboration for children in India (Jamil et al 2010). …”
Section: Indiamentioning
confidence: 99%
“…The layout of the elements were scattered in a circle around the centre point of the surface providing equal access to the elements for each participant. The spider diagram and classification activities were based on "Photosynthesis" and "Animals", both topics in the Indian National Curriculum (further description in [7][8]): using different learning activities and interaction techniques were intended to add richness to the study, and ensure that these findings were not dependent on a particular educational topic or interaction method.…”
Section: Study Description and Analysismentioning
confidence: 99%
“…What is central to these arguments is that learning is facilitated through encouraging all students to actively participate in exploring learning domains, discussing alternative ideas and perspectives, offering explanations, clarifications and justifications to each other and devising shared goals and plans of action, and thereby facilitating their understanding [1,13,28]. In light of these characteristics of collaborative learning, interactive tabletops have been argued to have various properties that promote the collaborative nature of these learning activities, for example, the ways that they organise groups around digital learning materials to encourage face to face discussion; how they enable simultaneous participation in collaborative learning, promote engagement and allow all students to share control and responsibility over the input and manipulation of learning materials; and how they make individual interactions at the tabletop visible to support shared awareness [6][7][8].…”
Section: Introductionmentioning
confidence: 99%